2019
DOI: 10.1088/1742-6596/1399/2/022057
|View full text |Cite
|
Sign up to set email alerts
|

The processes of hydrocarbon conversion using catalytic systems

Abstract: This article describes properties of the catalytic conversion of methane to synthesis gas, makes a review of information on the chemical composition of catalysts and provides assumptions about the mechanism of their action. The facts and generalizations given in the article can be useful in determining ways to improve catalytic systems. The most active and most selective catalytic systems make it possible to optimize existing processes by cutting down energy consumption, cost, emissions and increasing the yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To make it happen, not in words, but in reality, digital technologies must "serve" the entire society, but not its individual groups, estates, and clans. It is clear that the solution of economic problems with the help of digital technologies cannot by itself eliminate the disproportion of economic development, that is, to harmonize socially necessary needs and production possibilities (20)(21)(22)(23)(24)(25). But information technologies are able to create technological support for solving targets.…”
Section: Resultsmentioning
confidence: 99%
“…To make it happen, not in words, but in reality, digital technologies must "serve" the entire society, but not its individual groups, estates, and clans. It is clear that the solution of economic problems with the help of digital technologies cannot by itself eliminate the disproportion of economic development, that is, to harmonize socially necessary needs and production possibilities (20)(21)(22)(23)(24)(25). But information technologies are able to create technological support for solving targets.…”
Section: Resultsmentioning
confidence: 99%
“…The Yaregskiy oil was selected to study the possibility of extracting heavy metals from heavy oil. This oil belongs to the class of heavy (0.945 g/cm 3 ), high-viscosity (10,000-12,000 mPa•s at an initial temperature of 8 • C), low-sulfur and low-paraffin, and it contains a significant amount of heavy metals, e.g., vanadium, nickel, iron, titanium, noble and rare-earth metals [12][13][14][15][16][17][18][19][20][21][22][23]. The analysis of the initial sample and separation products was performed by atomic absorption, X-ray fluorescence, mass spectrometry with inductively coupled plasma, and instrumental neutron activation analysis (INAA) (St. Petersburg Konstantinov Institute of Nuclear Physics.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that some metals accumulate in large amounts in a number of cases compared to their clusters in the lithosphere. This allows us to estimate the economic and technological feasibility of these metals extraction from oil, while improving the quality of basic petroleum products [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of different metal catalysts for MDR have shown that noble metals such as Ru, Pd, Rh, Pt and Ir show a high catalytic activity [3,4]. A cheaper alternative to noble metals is the use of Nickel based catalysts, specifically systems that form catalytically active Nickel particles in reaction conditions such as Ni-doped Perovskites [5].…”
Section: Introductionmentioning
confidence: 99%